Transition metal oxide particles encapsulated in nanostructured lithium titanate or lithium aluminate, and the use thereof in lithium ion batteries
Patent Information
- Application Number
- KR1020210152039
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-11-11
- Filing Date
- 2021-11-08
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2041-11-08
Smart Images

Figure 112021128255112-PAT00001_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to a method for producing a transition metal oxide coated with a thermally generated lithium titanate and / or a thermally generated lithium aluminate, a coated transition metal oxide obtainable by this method, a cathode for a lithium-ion battery comprising such coated metal oxide, and a lithium-ion battery. Background Technology
[0002] Various energy storage technologies have recently attracted significant public attention and are the subject of intensive research and development in industry and academia. As energy storage technologies expand to devices such as mobile phones, camcorders, and laptop PCs, and further to electric vehicles, the demand for high-energy-density batteries used as power sources for these devices is increasing. Secondary lithium batteries are currently one of the most important battery types in use.
[0003] Secondary lithium batteries typically consist of an anode made of carbon material or a lithium-metal alloy, a cathode made of a lithium-transition metal oxide, and an electrolyte in which a lithium salt is dissolved in an organic solvent. The separator of the lithium battery provides a pathway for lithium ions between the positive and negative electrodes during the charging and discharging processes.
[0004] One of the common problems with cathode materials is their rapid aging and the consequent loss of performance during cycling. This phenomenon is particularly associated with nickel-manganese-cobalt mixed oxides (NMC) having a high nickel content. The deactivation of cathode materials occurs through various electrochemical decomposition mechanisms. These include transition metal rearrangement, as well as oxygen loss and Ni in a highly delithiated state. 4+Surface modifications, such as the formation of NiO-like phases due to the reduction of [substance], destabilize the crystal structure. This phase transition is associated with initial cracking and subsequent grain disintegration appearing on the cathode particle surface. Additionally, the electrolyte decomposes on the reactive surface of the NMC, and electrolyte decomposition products are deposited at the interface of the cathode material, which increases resistance. Furthermore, LiPF6, a conductive salt commonly used in liquid electrolytes, reacts with trace amounts of H2O present in all commercial formulations to form HF. This highly reactive compound causes lattice distortion in the cathode material through the dissolution of transition metal ions from the cathode material surface into the electrolyte. All of these decomposition mechanisms result in a reduction in capacity, performance, and cycle life.
[0005] It is known that coating transition metal oxide particles onto certain metal oxides suppresses unwanted reactions between the electrolyte and electrode materials, thereby improving the long-term lifespan stability of lithium batteries.
[0006] WO 00 / 70694 A1 discloses mixed transition metal oxide particles coated with oxides or mixed oxides of Zr, Al, Zn, Y, Ce, Sn, Ca, Si, Sr, Mg, and Ti. These are obtained by suspending uncoated particles in an organic solvent, mixing the suspension with a solution of a hydrolyzable metal compound and a hydrolysis solution, and then filtering, drying, and calcining the coated particles.
[0007] WO 2018149834A1 A1 discloses the preparation of encapsulated mixed transition metal oxide particles by drying mixing a metal oxide with a mixture of aluminum oxide and titanium dioxide generated exothermically.
[0008] Although these metal oxide additives used in the cathode coating have a positive effect on the long-term cycling stability of the electrode, they can degrade lithium ion diffusion, i.e., reduce the ionic conductivity of the electrode, resulting in a lower initial current.
[0009] Therefore, it would be desirable to have an electrode coating with particles that provide a protective function without reducing the ion conductivity of the electrode during the first charge / discharge cycle.
[0010] Two promising candidates for such conductive materials for electrode protection are lithium titanate (LTO) and lithium aluminate (LAO).
[0011] CN109830654 A is the cathode active material LiNi x Mn y Co z A lithium-ion battery cathode is disclosed, comprising a coating layer including at least one of O2 and MgO, Al2O3, ZrO2, TiO2, AlPO4, AlF3, LiAlO2, and LiTiO2. It has been reported that the coating layer increases the specific surface area of the cathode active material and prevents cathode metal ions from dissolving during the charging process, thereby improving the structural stability of the cathode active material. Specific examples using LiTiO2 are not described.
[0012] The literature [Int. J. Electrochem. Sci. vol. 8 (2013), pp. 2504–2514] describes the preparation of nanometer-sized Li2TiO3–LiCrO2 nanocomposite cathode powder by spray pyrolysis, thermal post-treatment, and subsequent washing with water. The average size of the mixed nanocomposite powder thus obtained, post-treated at 750°C, was 130 nm. The initial charge and discharge capacities of the nanocomposite powder and its capacity retention in a lithium-ion battery were tested. In this case, lithium titanate is a component distributed throughout the entire cathode powder particles obtained.
[0013] The literature [Journal of Power Sources vol. 174 (2007), pp. 1147-1151] describes Li4Ti5O under drying after sonication and calcination in air at 723 K for 10 h. 12 Surface treatment of a LiCoO2 cathode material with an ethanol dispersion of particles is described. The lithium titanate layer obtained in this way had an average thickness of 20 nm. These surface-treated LiCoO2 particles exhibited excellent cycle stability as a cathode in a battery cell. In this case, the use of an ethanol dispersion for LTO coating necessitates the handling of organic solvents and their subsequent removal. Furthermore, the shear force in the liquid medium is typically too low to crush the aggregated and clustered particles used, and to achieve excellent dispersibility on the coated material.
[0014] Gockeln (M. Gockeln) et al. report in the literature [Nano Energy, vol. 49 (2018), pp 564-573] the direct deposition of lithium titanate particles on polyimide / copper foil and the subsequent coating of the resulting composite foil on the surface of a lithium electrode after synthesis of lithium titanate particles via flame spray pyrolysis technology.
[0015] CN 109004201 A1 discloses a core-shell cathode for a solid-state lithium-ion battery based on a polymer substrate. The core structure of such a cathode is a lithium transition metal phosphate (LiMn x Fe (1-x) PO4, LiCoPO4, LiNiPO4), lithium manganate (LiMnO4), lithium transition metal oxide (LiNi 0.5 Mn 1.5 O4, LiNi x Co y Mn z It may include O2, Li2MnO3, and LiMO2 (M = Ni, Co, Mn). The shell structure is Li 1+x Al x Ti 2-x(PO4)3, Li 7-x La3Zr 2-x M x O 12 (M=Ta, Nb), Li x La 2 / 3-x TiO3, LiAlO2, Li2ZrO3, Li4Ti5O 12 It may include. The core-shell material is prepared by mechanical stirring. The particle size of the material used is somewhat large, for example, Li x La 2 / 3-x In the case of TiO3, it is 400 nm.
[0016] H. Cao et al., in the literature [Solid State Ionics, vol. 176 (2005), pp 911–914], C9H 21 We report the preparation of LiCoO2 coated with LiAlO2 and Al2O3 by drying and calcining an aqueous mixture of O3Al, LiOH, and LiCoO2 precursors. The electrochemical performance of the obtained material was also tested.
[0017] In the literature [Journal of Power Sources, vol. 239 (2013), pp 181 - 188], Mn 0.79 Ni 0.21 LiAlO2-surface modified LiMn by coating Al2O3 on a CO3 precursor, followed by post-sintering with Li2CO3 at 900°C 1.58 Ni 0.42 The synthesis of an O4 spinel cathode material has been reported. The electrochemical performance of the obtained material is also described.
[0018] For example, the use of lithium titanate and lithium aluminate in lithium-ion batteries for electrode coating is known from the prior art. However, the use of available nano-sized lithium titanate or lithium aluminate particles often results in heterogeneous distribution and large aggregated LTO and LAO particles on the surface of the core cathode material; consequently, minimal or no improvement in cycling performance is observed compared to the uncoated cathode material. LTO and LAO with very small average particle sizes have not yet been identified for widespread application in batteries. Furthermore, practical and economical coating methods for electrodes for lithium-ion batteries containing these particles have not been reported in the prior art to date.
[0019] Tasks and Solutions
[0020] The problem solved by the present invention is to provide a transition metal oxide modified with a lithium-ion conductive additive that improves the long-life stability of the lithium battery during operation, as a cathode material for use in lithium-ion batteries. As a coating for all established types of transition metal oxide materials, the ion conductive additive used should preferably be used in a relatively small amount.
[0021] Another problem solved by the present invention is to provide an efficient and economical method for achieving a homogeneous distribution of lithium-ion conductive additives having a small average particle size and a narrow particle size distribution on the surface of transition metal oxides. The metal oxide particles must be completely coated by the coating additive used. Larger non-dispersed aggregates and clusters of coating particles on the metal oxide surface must be avoided.
[0022] The described modified transition metal oxide particles must be suitable for use as a cathode for lithium-ion batteries in both liquid and solid-state electrolytes.
[0023] Through thorough experimental processes, it was confirmed that the use of a special type of coating method, so-called dry coating, for mixing exothermically generated lithium titanate and / or exothermically generated lithium aluminate and transition metal oxide particles provides a unique coated material that can be used as a cathode for a lithium-ion battery with increased performance.
[0024] Method for producing coated transition metal oxides
[0025] The present invention provides a method for producing a coated transition metal oxide, wherein the transition metal oxide and an exothermically generated lithium titanate and / or an exothermically generated lithium aluminate are applied to a dry mixture.
[0026] In the context of the present invention, "dry mixing" relates to a mixing method in which no liquid is added or used during the method, i.e., substantially dry powders are mixed together. However, it is possible for trace amounts of moisture or some liquid other than water to be present in the mixed feedstock, or for these to include crystallization water. Preferably, the mixture of transition metal oxide and exothermically generated lithium titanate and / or exothermically generated lithium aluminate contains less than 5 weight%, more preferably less than 3 weight%, and more preferably less than 1 weight% of water and / or other liquid.
[0027] The dry mixing method of the present invention has some advantages over wet coating, for example, coating with a dispersion containing lithium titanate and / or lithium aluminate. Such wet coating methods inevitably involve the use of a solvent that must be evaporated after the coating method is completed. Therefore, the dry coating method of the present invention is simpler and more economical than wet coating methods known from the prior art. On the other hand, surprisingly, it has been confirmed that the dry coating method of the present invention also provides a better distribution of lithium titanate and / or lithium aluminate particles on the surface of transition metal oxides.
[0028] In the method of the present invention, dry mixing is preferably performed by an electric mixing unit having a specific electrical power of 0.05 kW to 1.5 kW per 1 kg of transition metal oxide.
[0029] The term "electric mixing unit" in the context of the present invention relates to any mixing device operated by the supply of electric energy.
[0030] Power is the rate per unit time at which electrical energy is transmitted by an electric circuit. In the context of the present invention, the term "specific power" refers to the power supplied by an electric mixing unit during a mixing method, per 1 kg of transition metal oxide.
[0031] If the non-electrical power used is less than 0.05 kW per 1 kg of transition metal oxide, this typically results in a heterogeneous distribution of lithium titanate and / or lithium aluminate, which may not be firmly bonded to the core material of the transition metal oxide.
[0032] A non-electrical power of more than 1.5 kW per kg of transition metal oxide typically results in poorer electrochemical properties. Additionally, there is a risk that the coating will become brittle and prone to rupture.
[0033] The nominal power of the mixing unit can vary over a wide range, for example, from 0.1 kW to 1000 kW. Accordingly, a laboratory-scale mixing unit with a nominal power of 0.1 kW to 5 kW or a production-scale mixing unit with a nominal power of 10 kW to 1000 kW can be used. The nominal power is the maximum absolute power on the nameplate of the mixing unit.
[0034] Likewise, the volume of the mixing unit also ranges widely, for example, from 0.1 L to 2.5 m³ 3 It may vary. Therefore, a laboratory-scale mixing unit with a volume of 0.1 L–10 L or 0.1 m 3- 2.5 m 3 A mixing unit for a production scale having the volume of can be used.
[0035] In the context of the present invention, the term "volume of the mixing unit" refers to the maximum volume of the chamber of the electric mixing unit in which the material to be mixed may be placed.
[0036] Preferably, in the method according to the present invention, the forced mixer is used in the form of a powerful mixer having a high-speed mixing tool. It has been confirmed that a mixing tool speed of 5 m / s–30 m / s, more preferably 10 m / s–25 m / s, provides the best results. In the context of the present invention, the term “mixing tool” refers to any object within a mixing unit that is movable, for example, capable of rotation, shaking, etc., and thereby capable of mixing the contents of the mixing unit. Examples of such mixing tools are various types of agitators. Commercially available mixing units sufficiently suitable for the method of the present invention are, for example, Henschel mixers or Eirich mixers.
[0037] The mixing time is preferably 0.1 to 120 minutes, more preferably 0.2 to 60 minutes, and very preferably 0.5 to 10 minutes.
[0038] The method of the present invention may further include heat treatment of the coated transition metal oxide at a temperature of 300°C to 1400°C, preferably 400°C to 1200°C, more preferably 500°C to 1100°C. The duration of the heat treatment may be 10 minutes to 10 hours, preferably 0.5 hours to 5 hours, more preferably 1 hour to 3 hours. This heat treatment can improve the bonding of lithium titanate and / or lithium aluminate to the transition metal oxide.
[0039] However, in the method according to the present invention, since the exothermally generated lithium titanate and / or lithium aluminate typically adhere strongly to the transition metal oxide without any heat treatment, this treatment is not essential in this method. Accordingly, a preferred embodiment of the method according to the present invention does not include any heat treatment after mixing.
[0040] The proportion of lithium titanate and / or lithium aluminate is preferably 0.05 wt% to 5 wt%, more preferably 0.1 wt% to 2 wt%, with respect to the total weight of the mixture of the transition metal oxide and the lithium titanate and / or lithium aluminate. If the proportion of lithium titanate and / or lithium aluminate is less than about 0.05 wt%, beneficial effects of the coating cannot typically be observed. If the proportion exceeds 5 wt%, beneficial effects of the additional amount of lithium titanate and / or lithium aluminate cannot be observed.
[0041] Thermally generated lithium titanate and lithium aluminate
[0042] The lithium titanate (LTO) and / or lithium aluminate (LAO) used in the method according to the present invention is generated exothermically, which means that it is also generated by the additional modification of a precursor generated directly or exothermically by an exothermic method known as a "fumed" method, e.g., exothermally generated TiO2 or Al2O3. The terms "exothermally generated," "exothermic," and "fumed" are used as synonyms in the context of the present invention.
[0043] These "exothermic" or "fumed" methods involve forming compounds that are generated exothermically by the reaction of a corresponding metal precursor in flame oxidation or flame hydrolysis in an oxyhydrogen flame. This reaction initially forms highly dispersed, approximately spherical primary particles, which combine during further stages of the reaction to form aggregates. The aggregates can then accumulate as aggregates. Unlike aggregates, which can generally be separated into aggregates relatively easily by the introduction of energy, the aggregates are further decomposed only by the introduction of powerful energy, even if they are further decomposed. The particles can be partially destroyed by suitable grinding and converted into nanometer (nm) range particles, which are advantageous to the present invention. However, since the "manufactured" fumed particles have a sufficiently small particle size, such grinding is not required.
[0044] The lithium titanate used in the method of the present invention is preferably of the formula LiTiO2, Li2TiO3, Li2Ti3O7, Li4TiO4, Li4Ti5O 12 It is a compound of, or a mixture of, these.
[0045] A flame spray pyrolysis (FSP) method suitable for the production of lithium titanate may include the following steps:
[0046] 1) a step of atomizing at least one solution containing a titanium precursor and a lithium precursor, for example, by air or an inert gas, preferably using a multi-material nozzle, and
[0047] 2) a step of mixing combustion gases, preferably hydrogen and / or methane, and air, and
[0048] 3) A step of burning the mixture in a flame inside a reaction chamber enclosed by a casing,
[0049] 4) A step of cooling the high-temperature gas and solid product, and then removing the solid product from the gas.
[0050] Suitable for the production of LTO lithium precursors are, for example, lithium hydroxide, lithium oxide, lithium carbonate, lithium bicarbonate, lithium carboxylates, such as lithium oxalate, lithium acetate, lithium formate, lithium hexanoate, lithium heptanoate, lithium octoate, lithium 2-ethyl hexanoate, lithium decanoate, lithium neodecanoate, lithium dodecanoate, lithium nitrate, lithium chloride, lithium bromide, lithium sulfate, lithium perchlorate, and mixtures thereof.
[0051] Suitable titanium precursors are, for example, titanium nitrate, titanium chloride (IV), titanium oxychloride (IV), titanium (IV) oxysulfate, titanium (IV) oxynitrate, titanium alcoholate, e.g. tetramethyl orthotitanate, tetraethyl orthotitanate, tetrapropyl orthotitanate, tetra(iso-propyl) orthotitanate, and mixtures thereof.
[0052] Additional suitable Ti and Li metal precursors are metal carboxylates, in particular metal carboxylates of aliphatic carboxylic acids having 6 to 12 carbon atoms, for example, metal octoate or 2-ethylhexanoate, metal decanoate or metal dodecanoate.
[0053] Other than the Li and Ti metal precursors optionally used in the production of metal-doped LTO, the precursors may be inorganic materials, such as nitrates, chlorides, or organic compounds, such as carboxylates.
[0054] The metal precursor used may be soluble in water, organic solvents, or mixtures thereof. Suitable organic solvents include methanol, ethanol, n-propanol, isopropanol, n-butanol, tert-butanol, 2-propanone, 2-butanone, diethyl ether, tert-butyl methyl ether, tetrahydrofuran, C1-C12-carboxylic acids, such as 2-ethylhexanoic acid, ethyl acetate, toluene, petroleum, and mixtures thereof.
[0055] In the exothermic method for the production of lithium titanate, the ratio of titanium to lithium in the starting material can be adjusted to be equal to or slightly lower than the Ti to Li ratio of the desired lithium titanium compound. To compensate for the volatile loss of the Li salt during the production method, a slight excess of Li beyond the stoichiometric amount, for example, up to 10% more than the stoichiometric amount, may be added.
[0056] Lithium titanate can be further doped with metals other than lithium and titanium, such as aluminum (Al), lanthanum (La), etc.
[0057] Average particle diameter d of lithium titanate used in the production of coated transition metal oxides 50 When determined by static light scattering (SLS) after sonication of a 5 wt% dispersion of particles in water at 25°C for 60 s, the wavelength is preferably 10 nm-200 nm, more preferably 20 nm-150 nm, and even more preferably 30-120 nm.
[0058] Lithium aluminate is a compound with the chemical formula LiAlO2.
[0059] Lithium aluminate can be produced by a method comprising the following steps:
[0060] 1) A step of preparing an aqueous dispersion comprising fumed alumina, a lithium oxide precursor compound soluble in water, and an alkali metal carbonate and / or ammonium carbonate;
[0061] 2) A step of obtaining a dried powder by spray-drying the dispersion prepared in step 1);
[0062] 3) A step of calcining the dried powder obtained in step 2) at a temperature of 450℃ to 750℃.
[0063] A lithium aluminate primarily in the alpha crystallographic phase is preferably used in the method of the present invention. The term "alpha lithium aluminate" refers to the α-(hexagonal) allotropic form of the lithium aluminate. The term "allotropic form" is used in place of the term "crystallographic phase" in the present invention. The crystallographic structure of such a crystallographic phase (allotropic form) can be determined by XRD analysis. In the context of the present invention, "primarily in the alpha crystallographic phase" means that the lithium aluminate is at least 70% in the alpha phase when determined by XRD analysis. The lithium aluminate used comprises, preferably at least 80%, more preferably at least 90%, and more preferably at least 95% of the alpha LiAlO2 phase when determined by XRD analysis.
[0064] The term "soluble in water" refers to the solubility of at least 0.1 g, preferably at least 1.0 g, of the lithium oxide precursor compound in 100 g of water at 20°C in the context of the present invention.
[0065] A lithium oxide precursor compound that is soluble in water is preferably selected from the group consisting of lithium hydroxide, lithium oxide, lithium carbonate, lithium bicarbonate, lithium oxalate, lithium acetate, lithium formate, lithium nitrate, lithium chloride, lithium bromide, lithium sulfate, lithium perchlorate, and mixtures thereof.
[0066] The alkali metal carbonate is preferably selected from the group consisting of lithium carbonate, lithium bicarbonate, sodium carbonate, sodium bicarbonate, potassium carbonate, potassium bicarbonate, and mixtures thereof.
[0067] Ammonium carbonate may be a compound having the chemical formula (NH4)2CO3 (ammonium carbonate) or NH4HCO3 (ammonium bicarbonate).
[0068] Most preferably, both the lithium oxide precursor compound and the alkali metal carbonate are the same compound, lithium carbonate (Li2CO3).
[0069] The fumed alumina used in the manufacture of lithium aluminate is preferably 20 m 2 / g to 250 m 2 / g, more preferably 50 m 2 / g to 200 m 2 / g, more preferably 70 m 2 / g to 150 m 2 It has a BET surface area of / g. The BET surface area can be determined according to DIN 9277:2014 by nitrogen adsorption according to the Brunauer-Emmett-Teller procedure.
[0070] The aqueous dispersion used in step 1) of the method for manufacturing lithium aluminate comprises fumed alumina, a lithium oxide precursor compound soluble in water, and an alkali metal carbonate and / or ammonium carbonate. The content of fumed alumina in the dispersion is 0.5% to 20% by weight, more preferably 1% to 10% by weight, and more preferably 2% to 6% by weight.
[0071] The amount of lithium oxide precursor compound used preferably corresponds to the stoichiometric formation of LiAlO2, that is, the molar ratio of lithium to aluminum elements in the aqueous dispersion used in step 1) of the method is about 1 to 1.
[0072] In step 2) of the method, the dispersion prepared in step 1) is applied to spray drying to remove water and other volatile substances and to obtain a dried powder consisting of particles containing lithium and aluminum. Spray drying can be performed in any suitable spray dryer.
[0073] The dried powder obtained in step 2) of the method preferably has a numerical average particle size d of 20 μm or less, preferably 1 μm–15 μm, and more preferably 2 μm–10 μm. 50 Delivers particles having. Particle numerical average particle size d 50 It can be determined by static light scattering (SLS) in an aqueous dispersion.
[0074] These spray-dried particles preferably have a narrow particle size distribution. The width of the particle size distribution of these particles (d 90 -d 10 ) / d 50 It is preferably 2.5 or less, more preferably 0.8-2.0, and more preferably 0.9-1.5.
[0075] Step 2) of the method is preferably performed using an outlet air temperature of 50°C to 200°C, more preferably 80-150°C, and more preferably 90-140°C of a spray dryer.
[0076] In step 3) of the method, the dried powder obtained in step 2) of the method is calcined at a temperature of 450°C to 750°C, preferably 500°C to 700°C, more preferably 550°C to 650°C, and particularly preferably 580°C to 620°C to obtain alpha lithium aluminate.
[0077] The duration of step 3) may be 1 to 24 hours, preferably 2 to 20 hours, more preferably 3 to 10 hours, and more preferably 4 to 8 hours, depending on the applied firing temperature.
[0078] The firing in step 3) can be performed discontinuously, for example in a muffle furnace or using another suitable device, or continuously, for example in a rotary kiln or any other suitable device.
[0079] The obtained lithium aluminate can be further milled, preferably using a ball mill, to reduce the average particle size of the lithium aluminate.
[0080] Ball milling is preferably performed in a suitable solvent, such as ethanol or isopropanol, using ZrO2 balls having a diameter of, for example, about 0.5 mm.
[0081] The method described above for manufacturing lithium aluminate enables the production of lithium aluminate in an alpha crystallographic form having a high surface area, small particle size, and a narrow particle size distribution.
[0082] Numerical average particle size d of the lithium aluminate manufactured in this way 50 The size is typically 20 μm or less, preferably 1 μm-15 μm, more preferably 2 μm-10 μm.
[0083] Width of particle size distribution of lithium aluminate (d 90 -d 10 ) / d 50 It is preferably 2.5 or less, preferably 0.8-2.0, and more preferably 0.9-1.5.
[0084] The numerical average diameter of the primary particles of lithium aluminate, when determined by transition electron microscopy (TEM), is typically 1 nm to 100 nm, preferably 3 to 70 nm, more preferably 5 to 50 nm. This numerical average diameter can be determined by calculating the average size of at least 500 particles analyzed by TEM.
[0085] Accordingly, both the exothermally generated lithium titanate and lithium aluminate used in the method of the present invention are preferably characterized by high dispersibility, that is, the ability to form relatively small particles under mild ultrasonic treatment. It is believed that dispersion under such mild conditions corresponds to the conditions during the dry coating method. This means that the aggregate of lithium titanate and / or lithium aluminate can be broken down in the mixing method of the present invention in a manner similar to that under ultrasonic treatment, thereby forming a homogeneous coating of transition metal oxide.
[0086] Preferably, the particle diameter d of the lithium titanate and / or lithium aluminate used in the production of the coated transition metal oxide 90 When determined by static light scattering (SLS) after ultrasonic treatment of a 5 wt% dispersion of particles in water at 25°C for 60 s, the particle size is 500 nm or less, more preferably 300 nm or less, and even more preferably 200 nm or less.
[0087] The relatively low value d of the lithium titanate and / or lithium aluminate used 90 It ensures an extremely low proportion of large LTO and / or LAO particles, and also a very homogeneous distribution of lithium titanate and / or lithium aluminate on the surface of the transition metal oxide.
[0088] The exothermally generated lithium titanate and / or lithium aluminate used in the method of the present invention preferably features a relatively narrow particle size distribution and / or a relatively low content of both very fine (particle size < 10 nm) and large particles (particle size > 300 nm). This helps achieve a high-quality lithium titanate coating on the surface of a transition metal oxide. Large particles are undesirable as they prevent the formation of a homogeneous coating, whereas handling very fine particles often presents problems associated with dust formation.
[0089] value d10 , d 50 and d 90 is typically used to characterize the cumulative particle diameter distribution of a given sample. For example, d 10 The diameter is 10% of the sample volume d 10 A diameter consisting of particles of less than d 50 50% of the sample volume is d 50 It is the diameter composed of particles smaller than d. 50 It is also known as the "volume median diameter" as this divides the sample equally by volume; d 90 90% of the sample volume is d 90 It is a diameter consisting of particles smaller than [number].
[0090] The best results regarding the adhesion of lithium titanate and / or lithium aluminate to transition metal oxides are that lithium titanate and / or lithium aluminate is 10 m 2 / g-200 m 2 / g, more preferably 10 m 2 / g-100 m 2 / g, more preferably 20 m 2 / g-80 m 2 / g, also most preferably of 30 m 2 / g-60 m 2 It was confirmed that this is obtained when having a BET surface area of / g. The BET surface area can be determined according to DIN 9277:2014 by nitrogen adsorption according to the Brunauer-Emmet-Teller procedure.
[0091] Lithium titanate and / or lithium aluminate is preferably not surface-treated with any surface treatment agent, such as silane, after its synthesis by an exothermic method. The LTO and / or LAO particles thus produced typically have a purity of at least 96 weight%, preferably at least 98 weight%, and more preferably at least 99 weight%.
[0092] The lithium titanate and / or lithium aluminate used in the present invention preferably have a tamping density of 20 g / L-800 g / L, more preferably 50 g / L-500 g / L, even more preferably 100 g / L-400 g / L, and even more preferably 200 g / L-300 g / L.
[0093] The tamping density of powdered or coarse granular materials can be determined according to DIN ISO 787-11:1995 "General methods of test for pigments and extenders -- Part 11: Determination of tamped volume and apparent density after tamping". This involves measuring the apparent density of the layer after stirring and tamping.
[0094] Transition metal oxides
[0095] The term "transition metal" in the context of the present invention includes the following elements: Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Nb, Mo, Ru, Rh, Pd, Ag, Cd, Ta, W, Re, Os, Ir, Pt, Au. Preferably, the transition metal is selected from the group consisting of nickel, manganese, cobalt, and mixtures thereof.
[0096] The transition metal oxide preferably used in the method according to the present invention is selected from the group consisting of cobalt oxide, manganese oxide, mixed nickel-cobalt oxide, mixed nickel-manganese-cobalt oxide, mixed nickel-cobalt-aluminum oxide, mixed nickel-manganese oxide, or mixtures thereof.
[0097] The transition metal oxide preferably further comprises lithium and is of the general formula LiMO2 (wherein M is at least one transition metal selected from nickel, cobalt, and manganese; more preferably M = Co) or Ni x Mn y Coz (where 0.3 ≤ x ≤ 0.9, 0 ≤ y ≤ 0.45, 0 ≤ z ≤ 0.4).
[0098] The lithium transition metal oxide of general formula LiMO2 can be further doped with at least one other non-transition metal oxide, in particular aluminum oxide and / or titanium oxide and / or zirconium oxide.
[0099] Coated transition metal oxide
[0100] The present invention further comprises a core made of a transition metal oxide, and a number average particle size d of 10 nm–200 nm, preferably 20 nm–150 nm, more preferably 30 nm–30 nm. 50 Exothermally generated lithium titanate having, and / or a number average particle size d of less than 20 μm, preferably 1 μm–15 μm, more preferably 2 μm–10 μm, more preferably 2.5 μm–8.0 μm. 50 The present invention provides a coated transition metal oxide containing a shell comprising a thermogenically generated lithium aluminate having the following: The thermogenically generated lithium titanate and / or thermogenically generated lithium aluminate on the surface of the transition metal particles is in the form of aggregated primary particles. The number average particle size d of the thermogenically generated lithium titanate and / or thermogenically generated lithium aluminate in the coated mixed lithium transition metal oxide. 50 It can be measured by transmission electron microscopy (TEM) analysis. This number average particle size d 50 can be determined by calculating the average size of at least 500 particles analyzed by TEM. d obtained from TEM analysis 50The value is the average particle size d for the exothermically generated lithium titanate or exothermically generated lithium aluminate used in the method of the present invention, typically determined by static light scattering (SLS) after sonication of a 5 wt% dispersion of particles in water at 25°C for 60 s. 50 It is close to the value.
[0101] The coated transition metal oxide of the present invention is preferably obtained by the method described above according to the present invention.
[0102] The coated transition metal oxide of the present invention preferably has a numerical average particle diameter of 2 μm to 20 μm. The numerical average particle diameter can be determined according to ISO 13320:2009 by laser diffraction particle size analysis.
[0103] The coated transition metal oxide preferably has an LTO and / or LAO coating layer thickness of about 10 nm to 200 nm, as determined by TEM analysis.
[0104] The proportion of lithium titanate and / or lithium aluminate in the coated transition metal oxide is preferably 0.05 wt% to 5 wt%, more preferably 0.1 wt% to 2 wt%, with respect to the total weight of the transition metal oxide and the lithium titanate and / or lithium aluminate. If the proportion of lithium titanate and / or lithium aluminate is less than about 0.05 wt%, the beneficial effects of the coating cannot be typically observed. If the proportion exceeds 5 wt%, the beneficial effects of the additional amount of lithium titanate and / or lithium aluminate cannot be observed.
[0105] A further preferred feature of the exothermally generated lithium titanate and / or lithium aluminate used in the method of the present invention described above is also a preferred feature of the lithium titanate and / or lithium aluminate existing as a coating on a transition metal oxide, regardless of whether or not the coated transition metal oxide is generated by the method of the present invention.
[0106] Uses of coated transition metal oxides in lithium-ion batteries
[0107] The present invention further provides an active cathode material for a lithium-ion battery comprising a coated transition metal oxide according to the present invention.
[0108] The positive electrode of a lithium-ion battery, also known as a cathode, typically comprises a current collector and an active cathode material layer formed on the current collector.
[0109] The current collector may be aluminum foil, copper foil, nickel foil, stainless steel foil, titanium foil, a polymer substrate coated with a conductive metal, or a combination thereof.
[0110] The active cathode material may comprise a material capable of reversible intercalating / deintercalating of lithium ions, which is widely known in the relevant art. Such active cathode materials may comprise transition metal oxides, such as mixed oxides containing Ni, Co, Mn, V or other transition metals and optionally lithium. Particularly preferably, it is a mixed transition metal oxide (NMC) containing nickel, manganese, and cobalt.
[0111] The present invention also provides a lithium-ion battery comprising the coated transition metal oxide of the present invention.
[0112] The lithium-ion battery of the present invention may, in addition to the cathode, contain an anode, optionally a separator, and an electrolyte comprising a lithium salt or a lithium compound.
[0113] The anode of a lithium battery may comprise any suitable material commonly used in secondary lithium batteries that enables reversible inclusion / de-inclusion of lithium ions. Typical examples thereof include crystalline carbon such as natural or synthetic graphite in the form of plate-like, flake, spherical, or fibrous graphite; carbonaceous materials including amorphous carbon, such as soft carbon, hard carbon, mesophase pitch carbide, calcined coke, etc., or mixtures thereof. Additionally, lithium metal or a conversion material (e.g., Si or Sn) may be used as the anode active material.
[0114] The lithium-ion battery of the present invention may contain a liquid, gel, polymer, or solid electrolyte.
[0115] A liquid mixture of a lithium salt that is not cured, polymerized, or crosslinked and an organic solvent is referred to as a "liquid electrolyte" in the context of the present invention. A gelled or solid mixture comprising a cured, polymerized, or crosslinked compound or a mixture thereof, optionally a solvent, and a lithium salt is referred to as a "gel electrolyte" or a "polymer electrolyte." Such electrolytes may be prepared by polymerization or crosslinking of a mixture containing at least one reactive compound, namely a polymerizable or crosslinkable compound and a lithium salt.
[0116] The liquid electrolyte of a lithium-ion battery may include any suitable organic solvent commonly used in lithium-ion batteries, such as anhydrous ethylene carbonate (EC), dimethyl carbonate (DMC), propylene carbonate, methyl ethyl carbonate, diethyl carbonate, gamma butyrolactone, dimethoxyethane, fluoroethylene carbonate, vinylethylene carbonate, or a mixture thereof.
[0117] The electrolyte of a lithium-ion battery typically contains lithium salts. Examples of such lithium salts include lithium hexafluorophosphate (LiPF6), lithium bis-2-(trifluoromethylsulfonyl)imide (LiTFSI), lithium bis(fluorosulfonyl)imide (LiFSI), lithium perchlorate (LiClO4), lithium tetrafluoroborate (LiBF4), Li2SiF6, lithium trilate, LiN(SO2CF2CF3)2, and mixtures thereof.
[0118] The lithium-ion battery according to the present invention may also be of the solid-state type. Such a battery may include various types of solid electrolytes. The solid electrolyte of the lithium battery may include oxides, for example, lithium metal oxides, sulfides, phosphates, or solid polymers.
[0119] The present invention further provides a use of the coated transition metal oxide of the present invention in a lithium-ion battery, particularly as a component of the active anode of the lithium-ion battery. Brief explanation of the drawing
[0120] Figure 1 shows the particle size distribution of fumed LTO (a) and commercial "nano LTO" (b), analyzed by a laser diffraction particle size analyzer. Figure 2 shows SEM images comparing NMC dried coated with fumed LTO (a - backscattered electron (BSE) image, b - EDX mapping of Ti, c - high-resolution SEM image) with NMC dried coated with commercial "nano LTO" (d - BSE image, e - EDX mapping of Ti, f - high-resolution SEM image). Figure 3 shows SEM images comparing NMC dried coated with fumed LTO (a - BSE image, b - EDX mapping of Ti, c - high-resolution SEM image) with NMC wet coated with fumed LTO (d - BSE image, e - EDX mapping of Ti, f - high-resolution SEM image). Figure 4 shows the cycling performance of uncoated NMC, NMC dry-coated with commercial "nano LTO", as well as NMC wet-coated and dry-coated with 1 wt% fumed LTO NMC in a lithium-ion battery with a liquid electrolyte. FIG. 5 shows the rate performance at 0.1C to 2C of uncoated NMC and NMC coated with 0.5 wt%, 1 wt%, and 2 wt% fumed LTO in a full-solid-state lithium-ion battery (System: Li6PS5Cl-NMC-VGCF || Li6PS5Cl || Li-In). Figure 6 shows the cycling performance over 100 cycles of uncoated NMC and NMC coated with 2 wt% fumed LTO (System: Li6PS5Cl-NMC || Li6PS5Cl || Li-In). Figure 7 shows the rate performance at 0.1C to 2C of uncoated NMC and NMC coated with 1 wt% Aeroxide® Alu 65, Aeroxide® Alu 130, and nanostructured LiAlO2 powder in a full-solid-state lithium-ion battery (System: Li6PS5Cl-NMC-VGCF || Li6PS5Cl || Li-In). Specific details for implementing the invention
[0121] Examples
[0122] Starting material:
[0123] 47 m 2 Fumed lithium titanate Li4Ti5O with a specific surface area (BET) of 1 / g 12 (LTO) was prepared by the flame spray pyrolysis method.
[0124] 5.1 m 2Commercial "nano LTO" powder having a BET surface area of 1 / g was provided by SAT nano technology material Co. LTD.
[0125] 0.30-0.60 m 2 BET surface area of / g, median diameter d 50 Commercial nickel manganese cobalt mixed oxide powder NMC 7 1.5 1.5 with = 10.6 ± 2 μm (determined by laser scattering method) (Linyi Gelon LIB Co., Type PLB-H7).
[0126] Figure 1 shows the particle size distribution of fumed LTO (a) and commercial "nano LTO" (b), analyzed by a laser diffraction particle size analyzer. Samples were dispersed in distilled water and treated in an external ultrasonic bath (160 W) for 15 minutes. For fumed LTO, a mono-modal and very narrow particle size distribution was detected (Figure 1a), whereas for commercial "nano LTO," a significantly larger average particle size and a wider particle size distribution were characteristic (Figure 1b).
[0127] Fumed Lithium Titanate Li 4 Ti 5 O 12 Manufacturing of (LTO)
[0128] 3911.3 g of a commercial solution containing 2 wt% lithium in the form of lithium neodecanoate dissolved in naphtha (Borchers® Deca Lithium 2), 4107.3 g of a commercial solution containing 16.5 wt% Ti in the form of tetrapropylorthotitanate (TIB Kat 530), and 10.5 kilograms of a solution containing 2485 g of ethanol. This solution is Li4Ti5O 12 Corresponding to the composition of.
[0129] 2.5 kg / h of this dispersion and 15 Nm 3 An air aerosol at 1 / h was formed through a two-component nozzle and sprayed into a tubular reactor along with a combustion flame. The combustion gas of the flame was 10 Nm³ 3 Hydrogen / h and 55 Nm 3 It consisted of air at / h. Additionally, 40 Nm 3 Secondary air at 1 / h was used. After the reactor, the reaction gas was cooled and filtered. The particle size distribution of this powder is shown in Fig. 1a.
[0130] LiAlO 2 Manufacturing of (LAO)
[0131] 60 g of exothermic aluminum oxide aerooxide® Alu C (Evonik Industries AG) was dispersed in a solution of 84 g (NH4)2CO3 in 900 g of water. A stoichiometric amount of LiOH solution was added to obtain LiAlO2 in 500 g of water. This dispersion was spray-dried in a laboratory spray dryer (Buechi T0630) with an inlet air temperature of 230°C and an outlet air temperature of 130°C. The resulting powder was subjected to calcination at 600°C for 6 hours. The resulting powder was 64 m 2 It had a BET surface area of / g.
[0132] Example 1:
[0133] First, NMC powder was mixed with each amount (1.0 wt%) of fumed LTO powder in a high-intensity laboratory mixer (SOMAKON mixer MP-GL with a 0.5 L mixing unit) at 500 rpm for 1 min to ensure homogeneous mixing of the two powders. Then, the mixing intensity was increased to 2000 rpm for 5 min to achieve dry coating of NMC particles with LTO.
[0134] The thickness of the LTO coating layer on the NMC particles was about 15-200 nm.
[0135] Comparative Examples 1
[0136] The procedure was the same as that of Example 1, except that commercial "nano LTO" powder was used instead of fumed LTO powder.
[0137] Comparative Examples 2
[0138] Fumed LTO (0.50 g) was milled in toluene (150 mL) using a high-shear rotor-stator mixer (Polytron PT 6100) at 25,000 rpm for 30 min. NMC powder (50.0 g) was suspended in toluene (100 mL). Then, the LTO suspension was added dropwise to the NMC suspension under stirring. This mixture was stirred for an additional 15 min. The solvent was removed by evaporation, and the residual powder was dried under vacuum at room temperature.
[0139] Figure 2 shows SEM images of NMC dry-coated with LTO (Figure 2 a, b, c: fumed LTO, d, e, f: commercial "nano LTO"). A comparison of the backscattered electron image (a) of the NMC dry-coated with fumed LTO and the EDX mapping of Ti (b) reveals a complete and homogeneous coating of all cathode particles with fumed LTO. No larger LTO aggregates were detected, indicating that excellent dispersion of nanostructured fumed LTO particles was achieved. Additionally, no unattached free LTO particles appeared next to the cathode particles, indicating strong adhesion between the coating and the substrate. The high-resolution SEM image (c) shows a homogeneous distribution of fumed LTO with a high surface coating of CAM.
[0140] In contrast, a comparison of the material contrast image (d) of NMC dry-coated with commercial "nano LTO" and the EDX mapping of Ti (e) shows that the larger LTO particles are almost non-dispersed and therefore located next to the cathode particles without being attached. The high-resolution SEM image (f) shows that only a small portion of the LTO particles are attached to the surface of the cathode material. As a result, the NMC particles are coated with LTO only sparsely.
[0141] Figure 3 shows SEM images comparing NMC (a, b, c) dry-coated with fumed LTO with NMC (d, e, f) wet-coated with fumed LTO.
[0142] Backscatter image (d) of NMC wet-coated with fumed LTO and EDX mapping of Ti (e) show that the shear force in the liquid medium is not sufficient to completely de-aggregate the fumed LTO aggregates. As a result, larger LTO aggregates exist next to the cathode particles. The NMC particles are only sparsely coated with a heterogeneous LTO coating layer (high-resolution image f).
[0143] Electrochemical testing of lithium-ion batteries with liquid electrolytes
[0144] Electrodes for electrochemical measurements were prepared by blending 90 wt% NMC with 5 wt% PVDF (Solef PVDF 5130) as a binder and 5 wt% SUPER PLi (TIMCAL) as a conductive additive under an inert gas atmosphere. N-methyl-2-pyrrolidone (NMP) was used as a solvent. The slurry was cast onto aluminum foil and dried in air on a heating plate at 120°C for 20 min. Subsequently, the electrode sheet was dried in a vacuum furnace at 120°C for 2 h. A circular electrode with a diameter of 12 mm was punched, calendered at a pressure of 90 psi, and dried again in a vacuum furnace at 120°C for 12 h to remove any residues and NMP. For the cycling test, the cell was assembled as a CR2032 type coin cell (MTI Corporation) in an argon-charging glove box (GLOVEBOX SYSTEMTECHNIK GmbH). Lithium metal (ROCKWOOD LITHIUM GmbH) was used as the anode material. Celgard 2500 was used as the separator. 25 μL of a 1 M solution of LiPF6 in ethylene carbonate and ethyl methyl carbonate (50:50 wt / wt; SIGMA-ALDRICH) was used as the electrolyte. The cell was locked with a crimper (MTI).
[0145] For electrochemical evaluation, constant current cycling was performed at 3.0 to 4.3 V. For the calculation of capacity and specific current, only the mass of the active material was considered. During cycling, for the coin half-cell, the C-rate was increased every 4 cycles, starting from 0.1 / 0.1 (charge / discharge) to 0.3 / 0.3, 0.5 / 0.5, 1.0 / 1.0, 1.0 / 2.0, and 1.0 / 4.0 C. Subsequently, the cell was cycled at 0.5 / 0.5 C for long-term stability testing.
[0146] Figure 4 illustrates the effect of the LTO coating layer on cycling performance. The performance of NMC dry-coated with fumed LTO is compared with that of NMC dry-coated with commercial "nano LTO" and NMC wet-coated with fumed LTO. The cycling performance of the uncoated NMC is shown for reference. From the graphs presented, it can be easily recognized that the dry-coated fumed LTO coating provides the most superior improvement in the stability and cycle life of the NMC. NMC dry-coated with fumed LTO exhibits a higher discharge capacity across all cycles of the initiation rate test and long-term cycling test. It also exhibits a higher initial specific discharge capacity at 0.1C than the other samples. Cells with NMC dry-coated with commercial "nano LTO" and NMC wet-coated with fumed LTO exhibit significantly worse cycling performance. Their rate performance is much worse than that of the uncoated NMC. Only long-term cycling performance is slightly improved compared to uncoated NMC, but it is still worse than the performance of NMC dried coated with fumed LTO.
[0147] Example 2
[0148] NMC powder was first mixed with fumed LTO powder in respective amounts (0.5 wt%, 1.0 wt%, and 2 wt%) in a high-intensity laboratory mixer (Somakon mixer MP-GL with a 0.5 L mixing unit) at 500 rpm for 1 minute to ensure homogeneous mixing of the two powders. Subsequently, the mixing intensity was increased to 2000 rpm for 5 minutes to achieve a dry coating of the NMC particles with LTO. The thickness of the LTO coating layer on the NMC particles was approximately 20-200 nm.
[0149] Electrochemical testing of lithium-ion batteries with solid electrolytes
[0150] A Li6PS5Cl-NMC-VGCF || Li6PS5Cl || Li-In all-solid-state lithium-ion battery (ASSLIB) was fabricated using Li6PS5Cl-NMC-VGCF as the cathode, Li6PS5Cl as the solid electrolyte, and Li-In foil as the anode. The electrolyte layer was obtained by manually compressing Li6PS5Cl powder in a poly(ether-ether-ketone) mold with a diameter of 12 mm. Subsequently, the cathode composite powder was pressed onto the top of a pellet at ~380 MPa. The cathode composite loading was approximately 15.3 mg × cm⁻¹. -2 ...was. Subsequently, Li-In foil was attached to the other side of the pellet as an anode. Finally, an external frame is used around the battery casing by applying a constant pressure of ~50 MPa. The electrochemical performance of the all-solid-state cell was tested using the (pellet-type) battery casing manufactured in-house. Constant current cycling was performed at 2.0 to 3.7 V (vs. Li + / Li-In) was performed. For the calculation of capacity and specific current, only the mass of the active material was considered. During cycling, the C-rate was increased starting from 0.1 / 0.1 (charge / discharge) to 0.25 / 0.25, 0.5 / 0.5, 1.0 / 1.0, and 2.0 / 2.0 (3 cycles for each up to 0.5C and 5 cycles for each from 1.0C to 2.0C). Subsequently, the battery was cycled at 0.25 / 0.25C for a long-term stability test at 25°C.
[0151] Figure 5 shows the cycling performance over approximately 20 cycles of NMC coated with 0.5 wt%, 1 wt%, and 2 wt% fumed LTO in Li6PS5Cl-NMC-VGCF || Li6PS5Cl || Li-In ASSLIB compared to the performance of uncoated NMC as a reference. Significantly improved cycling performance was achieved in all coated NMCs. In Figure 6, NMC dry-coated with fumed LTO exhibits a higher discharge capacity over 100 cycles compared to uncoated NMC. The best performance was obtained by NMC coated with fumed LTO at a coating ratio of 1 / 2 wt%.
[0152] Comparative Examples 3
[0153] The procedure was the same as that of Example 2, except that Aeroxid® Alu 65 (manufacturer: Evonik Industries AG) powder containing 1.0 wt% was used instead of fumed LTO powder.
[0154] Comparative Examples 4
[0155] The procedure was the same as that of Comparative Example 2, except that Aeroxid® Alu 130 powder (manufacturer: Evonik Industries AG) containing 1.0 wt% was used instead of fumed LTO powder.
[0156] Example 3
[0157] The procedure was the same as that of Example 2, except that nanostructured LiAlO2 powder with 1.0 wt% was used instead of fumed LTO powder.
[0158] Figure 7 shows the rate performance of NMC coated with 1 wt% Aeroxid® Alu 65, Aeroxid® Alu 130, and nanostructured LiAlO2 powder in Li6PS5Cl-NMC-VGCF || Li6PS5Cl || Li-In ASSLIB compared with the performance of uncoated NMC as a reference. The best performance was obtained by NMC coated with nanostructured LiAlO2 powder at a coating ratio of 1 wt%.
Claims
Claim 1 A transition metal oxide selected from the group consisting of cobalt oxide, manganese oxide, mixed nickel-cobalt oxide, mixed nickel-manganese-cobalt oxide, mixed nickel-cobalt-aluminum oxide, mixed nickel-manganese oxide, or mixtures thereof, and an exothermically generated formula LiTiO2, Li2TiO3, Li2Ti3O7, Li4TiO4, Li4Ti5O 12 A method for producing a coated transition metal oxide, characterized by applying a lithium titanate or a mixture thereof and / or a lithium aluminate of the chemical formula LiAlO2, which is generated exothermically, to a dry mixture. Claim 2 A method according to claim 1, characterized in that the dry mixing is performed by an electric mixing unit having a non-electric power of 0.05 kW to 1.5 kW per 1 kg of transition metal oxide. Claim 3 In claim 1 or 2, the BET surface area of the lithium titanate or lithium aluminate used for the production of the coated transition metal oxide is 10 m² 2 / g-200 m 2 A method characterized by being / g. Claim 4 In claim 1 or 2, the average particle diameter d of the lithium titanate particles used in the production of the coated transition metal oxide. 50 A method characterized by the particle size being 10 nm to 200 nm when determined by static light scattering (SLS) after sonication of a 5 wt% dispersion of particles in water at 25°C for 60 s. Claim 5 In claim 1 or 2, the average particle diameter d of the lithium aluminate particles used in the production of the coated transition metal oxide. 50 A method characterized by having a particle size of less than 20 μm when determined by static light scattering (SLS) after ultrasonic treatment of a 5 wt% dispersion of particles in water at 25°C for 60 s. Claim 6 A method according to claim 1 or 2, further comprising heat treatment of a coated transition metal oxide at a temperature of 300℃-1400℃. Claim 7 A method according to claim 1 or 2, characterized in that the ratio of lithium titanate and / or lithium aluminate is 0.05 wt% to 5 wt% with respect to the total weight of the mixture of transition metal oxide and lithium titanate and / or lithium aluminate. Claim 8 A core composed of transition metal oxides, and a number average particle size d of 10 nm–200 nm as determined by TEM analysis 50 Exothermally generated lithium titanate having, and / or a number average particle size d of less than 20 μm 50 A coated transition metal oxide containing a shell comprising a thermally generated lithium aluminate having Claim 9 An active cathode material for a lithium-ion battery comprising a coated transition metal oxide according to claim 8. Claim 10 A lithium-ion battery comprising a coated transition metal oxide according to claim 8. Claim 11 In paragraph 10, a lithium-ion battery containing a liquid, gel, or polymer electrolyte. Claim 12 In Clause 10, a solid-state type lithium-ion battery. Claim 13 A method of using a coated transition metal oxide according to claim 8 in a lithium-ion battery. Claim 14 delete Claim 15 delete